Enhancing climate forecasting in West Africa and the Sahel - Segnon, Alcade (2024)
Thanks to AICCRA capacity building on Next Generation (NextGen) seasonal climate forecast systems, the AGRHYMET Regional Climate Centre for West Africa and the Sahel has adopted an objective, traceable, and reproducible seasonal forecasting procedure that enables the generation of improved seasonal forecasts. The NextGen approach is fully operational at AGRHYMET, and NextGen forecasting products are being used to upgrade the AGRHYMET climate information portal. AGRHYMET has also transferred the newly acquired technical capacities to 173 participants from 17 National Meteorological and Hydrological Services in West Africa and the Sahel, enabling them to generate timely and decision-relevant climate information for agricultural sectors in West Africa.